Effect of Breast Milk Oral Care on Mechanically Ventilated Preterm Infants: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Cai, Meiling; Lin, Lingyu; Peng, Yanchun; Chen, Liangwan; Lin, Yanjuan (Frontiers in Pediatrics, 2022)
Background: The benefits of breast milk oral care in mechanically ventilated preterm infants remain controversial. This study aimed to systematically review the evidence on the benefits of breast milk oral care in mechanically ventilated preterm infants. Methods: The randomized controlled trials of breast milk oral care for mechanically ventilated preterm infants were searched in EMBASE, PubMed, Cochrane Library, Web of Science, WANFANG Date and China National Knowledge Infrastructure databases. The retrieval language was limited to Chinese and English, and the final search was conducted until March 2022. Outcome measures included ventilator-associated pneumonia (VAP), mechanical ventilation time (MVT) , length of stay (LOS), necrotizing enterocolitis (NEC), late-onset sepsis, mortality during hospitalization, time of full intestinal feeding and time of full oral feeding. Two researchers independently screened the literature, extracted the data, and conducted the literature quality assessment. Meta-analysis was mainly performed using Revman5.3. Results: Eight articles involving 1046 preterm infants were included. Our meta-analysis showed that compared with the control group, breast milk oral care could reduce the incidence of VAP [RR = 0.41, 95% CI (0.23, 0.75), P = 0.003] and NEC [RR = 0.54, 95% CI (0.30, 0.95), P = 0.03], and shorten the MVT [MD = -0.45, 95% CI (-0.73, -0.18), P = 0.001] and LOS [MD = -5.74, 95% CI (-10.39, -1.10), P = 0.02]. There were no significant differences in the mortality during hospitalization [RR = 0.94, 95% CI (0.67, 1.33), P = 0.74], the incidence of late-onset sepsis [RR = 0.79, 95% CI (0.40, 1.59), P = 0.51], the time of full intestinal feeding [MD = -2.42, 95% CI (-5.37, 0.52), P = 0.11] and the time of full oral feeding [MD = -3.40, 95% CI (-10.70, 3.91), P = 0.36] between the two groups. Conclusions: Oral care of breast milk can reduce the incidence of VAP and NEC, shorten MVT and LOS in mechanically ventilated preterm infants. However, due to the quality and quantity limitations of the included studies, larger sample size and more strictly designed clinical trials are still needed in the future to further confirm the findings of this study.